Learning Networks and the Practice of Wisdom. (October 2014) - Marshall, Nick; Simpson, Barbara
Learning networks offer a context and methodology for business managers to learn from each other's experience. However, the extent to which these networks can facilitate and support wise action remains an open question. In this article, we adopt a Buddhist perspective on wise action as a counterpoint to more familiar Western notions of wisdom as accumulated knowledge. We apply this novel perspective to a case example drawn from a learning network of small and medium-sized enterprises, demonstrating that the Buddhist focus on interdependent origination and impermanence suggests specific ways of working together that can enhance the practice of wisdom in, and beyond, learning networks.